FALL ILLEGAL KILL OF FEMALE WILD TURKEYS IN VIRGINIA AND WEST VIRGINIA - Gary W. Norman; James C. Pack; David E. Steffen; Curtis I. Taylor (Wildlife Society Bulletin)
Abstract: State wildlife agencies recognize illegal kill of eastern wild turkeys (Meleagris gallopavo silvestris) occurs but the extent of losses are often unknown. As part of a 5‐year cooperative study of population dynamics of female wild turkeys in our region, we radio‐tagged 1,032 females from 3 separate areas to determine survival and sources of mortality including known illegal and potential illegal deaths. Fall turkey seasons and other big and small game seasons varied between our states and we sought to identify potential patterns of illegal kill related to different fall turkey hunting seasons. Annual and fall‐winter mortality rates from known illegal deaths were not significantly different among our study areas. Known illegal mortality rate in the fall‐winter period, averaged for the 3 study sites over 5 years, was 0.05. Patterns of illegal mortality during the fall hunting seasons were similar among our study sites. We used a model selection procedure to determine that mast abundance influenced illegal mortality rates during the fall hunting seasons. Law enforcement agencies may improve effectiveness in apprehension of turkey poachers by timing enforcement efforts to coincide with patterns of illegal kills, particularly during years of mast failures. We recommend several changes in outreach to hunters, which may reduce illegal killing of hens.